Diagnosis of Noise Inside Neonatal Incubators under Free-Field Conditions - Francisco Fernández-Zacarías; Juan Luis Beira-Jiménez; Virginia Puyana-Romero; Ricardo Hernández-Molina (Acoustics, 2023)
The study aims to diagnose the sound pressure levels inside incubators in a controlled environment under free-field conditions. The tests were carried out in a semi-anechoic room under the standard UNE-EN ISO 3745:2012/A1:2018 in three different operating states: off, on, and on with a temperature alarm triggered. Sound pressure levels were analyzed in three different models of incubators, both inside and outside. The main noise indices analyzed were the corrected equivalent continuous level (LKeq) and the equivalent continuous level (Leq) in third-octave bands. The results obtained under normal operating conditions showed variations among the different incubators, with overall values between 48.8 and 56.3 dBA. The influence of the alarm considerably worsened these data. The values obtained showed that premature newborns are exposed to noise levels above international recommendations. All incubators tested showed the presence of tonal components, both outside and inside the incubator cabin, and, in some cases, low-frequency components, but no impulsivity components were observed in any case.